Groundwater recharge mechanisms inferred from isoscapes in a complex tropical mountainous region - Ricardo Sánchez‐Murillo; Christian Birkel (Geophysical Research Letters)
Abstract Stable isotope variations and groundwater recharge mechanisms remain poorly understood across the tropics, particularly in Central America. Here stable isotopes (δ18O and δ2H) in groundwater, surface water, and rainfall are used to produce high‐resolution (100 m2 grid) isoscapes for Costa Rica, from which an isotope ratio of precipitation to groundwater (P/GW) is estimated to elucidate the dominant groundwater recharge processes. Spatially, groundwater and surface water isotope ratios depict the strong orographic separation into the Caribbean and Pacific slopes induced by moisture transport directly from the Caribbean Sea and the eastern tropical Pacific Ocean. P/GW isotope ratios reveal that groundwater recharge is biased toward intensive and more depleted monthly rainfall across the Pacific slope with clear evidence of secondary evaporation indicating slower soil matrix recharge processes. On the other hand, P/GW isotope ratios indicate a weak influence of secondary evaporation across the Caribbean slope suggesting rapid recharge via preferential flow paths.